Ontología orientada a las máquinas: del siglo XIX al realismo especulativo - Sandrone, Darío; Lawler, Diego (Mechane, 2021)
In this article we argue in favor of this suggestion: Speculative Realism provides some basic philosophical premises to give machines a chance to exist, to rescue and update a realist tradition on complex technological phenomena that began in the 19th century, continues in the 20th century and challenges the machines of today’s world. Firstly, we present some basic elaborations of Speculative Realism to give an account of technical objects. Secondly, we propose a realistic interpretation of the theoretical developments around machines in the 19th century, present in the elaborations of Charles Babbage, Karl Marx, Robert Willis and Franz Realux. Finally, we identify a continuity between these conceptions of the machine and the project of a mechanology promoted at the beginning of the 20th century by the developments of Jacques Laffite and Gilbert Simondon. This journey leads us to affirm that there are certain relevant continuities between the principles of Speculative Realism and the elaboration of a realistic ontology of machines.